Indications and outcomes of radial head excision: A systematic review. (June 2020) - Hildebrand, Alexandra H; Zhang, Betty; Horner, Nolan S; King, Graham; Khan, Moin; Alolabi, Bashar
Background: Radial head excision has historically been a common surgical procedure for the operative management of radial head fractures and post-traumatic conditions. With recent advances in other surgical techniques, controversy exists regarding its indications. This review evaluates the indications and outcomes of radial head excision in traumatic and non-traumatic elbow pathology. Methods: Multiple databases were searched for studies involving radial head excision. Screening and data abstraction were conducted in duplicate. Only studies reporting outcomes for radial head excision were included. Results: Twenty-seven studies with 774 radial head excision patients were included. The most common indications involved acute excision of comminuted radial head fractures (n = 347) and rheumatoid arthritis (n = 201). Post-operative functional scores after acute excision were reported to be good to excellent. In the chronic setting of rheumatoid disease, radial head excision resulted in improved range of motion, although pain was not effectively relieved. Discussion: Outcomes of radial head excision for acute fracture are good to excellent; however, it should not be performed when concurrent or ligamentous injuries are present. Although some studies compared excision to open reduction and internal fixation or replacement, more data are needed to make proper conclusions. The strength of these conclusions is limited by the quality of included literature.